OCTA-based evaluation of the correlation between macular retinal and choroidal structural characteristics and refractive status in patients with retinopathy of prematurity - Chen, Chen; Hong, Liu (Frontiers in Pediatrics, 2025)
PurposeTo investigate the correlation between macular retinal and choroidal structural characteristics and refractive status in preschool-aged children with retinopathy of prematurity (ROP), based on optical coherence tomography angiography (OCTA), and to analyze the relationship between serum vascular endothelial growth factor (VEGF) levels and microcirculatory alterations.Methods310 preterm children with a history of ROP who were followed up at our hospital between January 2022 and June 2024 were included. According to the International Classification of Retinopathy of Prematurity (ICROP), participants were categorized into mild (n = 150, stage 1–2 ROP not meeting treatment criteria), moderate (n = 150, pre-threshold stage 3 ROP requiring treatment), and severe (n = 10, stage 3 threshold or above, or cases with retinal detachment) groups. Foveal avascular zone (FAZ) area, vessel densities of the superficial capillary plexus (SCP) and deep capillary plexus (DCP), choroidal thickness, number of vascular branches, vascular tortuosity, and foveal thickness were evaluated. Refractive parameters and VEGF levels were measured. The correlation between OCTA parameters, refractive parameters, and serum VEGF levels was analyzed.ResultsThe myopia rate in the severe group (80.0%) was higher than that in the moderate (52.0%) and mild (18.7%) groups (χ² = 68.45, P < 0.001). The spherical equivalent (SE) was (−2.35 ± 2.75) D, (−0.85 ± 2.15) D, and (+0.75 ± 1.25) D in the severe, moderate, and mild groups, respectively (F = 45.32, P < 0.001). The FAZ area was negatively correlated with the SE (r = −0.659, P < 0.001) and positively correlated with the axial length (r = 0.653, P < 0.001). The SCP vessel density was positively correlated with the SE (r = 0.618, P < 0.001). The choroidal thickness was positively correlated with the SE (r = 0.655, P < 0.001). Multivariable logistic regression analysis showed that a history of severe ROP (OR = 3.85, 95% CI: 2.52–5.86), SCP vessel density <40% (OR = 2.58, 95% CI: 1.78–3.76), FAZ area >0.35 mm² (OR = 2.24, 95% CI: 1.55–3.25), and choroidal thickness <250 μm (OR = 2.32, 95% CI: 1.62–3.36) were associated with the development of myopia. Serum VEGF level was positively correlated with FAZ area (r = 0.375, P < 0.001) and negatively correlated with SCP vessel density (r = −0.419, P < 0.001).ConclusionIncreased FAZ area, decreased SCP vessel density, and decreased choroidal thickness were associated with the development of myopia. Serum VEGF levels were correlated with macular microcirculatory parameters.